Nanoarchitectonics at Interfaces for Regulations of Biorelated Phenomena: Small Structures with Big Effects. Issue 6 (31st March 2021) - Ariga, Katsuhiko
Abstract : Syntheses, analyses, and controls of small structures have been paid much attention to in recent research activities. Architecting appropriate small structures into rational organization is the promising methodology to produce functional material systems with high performances. This important role is assigned to an emerging concept, nanoarchitectonics, which is supposed to produce functional material systems from nanoscale units through fusion of nanotechnology with the other related fields such as supramolecular chemistry, organic chemistry, materials science, and biorelated technology. Herein, interfacial nanoarchitectonics strategies for regulation of biorelated phenomena by small structural controls are described with the classification of interfacial types: rigid solid interfacial nanoarchitectonics and flexible liquid interfacial nanoarchitectonics. In addition to general tendencies seen in recent research, several detailed examples, such as regulation of self‐renewal with multipotency for stem cell on nanostructured surfaces, fate control of stem cell at liquid−liquid interface, and biolike metamorphosis with nonbio‐assembly at liquid−liquid interface, are described. These examples strikingly indicate that small structures at interfaces regulate big bioeffects including living cell fates. Abstract : Herein, interfacial nanoarchitectonics strategies for regulation of biorelated phenomena by small structure controls are described, including regulation of self‐renewal with multipotency for stem cell, fate control of stem cell at liquid−liquid interface, and biolike metamorphosis with nonbio‐assembly at liquid−liquid interface. These examples strikingly indicate that small structures at interfaces regulate big bio‐effects including living cell fates.